Inheritance of high prolificacy of the Olkuska sheep (preliminary results) - Radomska, M. J.; Martyniuk, E.; Klewiec, J. (Agricultural and Food Science, 1988)
Studies are being conducted on the mode of inheritance of high reproductive performance of the Olkuska (O) sheep, a local Polish breed. Ten O were used in crosses with Polish Merino (PM) ewes. The ovulation rate of 60 F1 ewes (O x PM) and 129 pure PM ewes was stated by means of laparoscopy. The prolificacy of female ancestors, full-sisters and progeny of 3 O rams was extensively analysed.